Fallen Grace - Hooper, Mary 1944- (Bloomsbury, 2010)
In Victorian London, impoverished fifteen-year-old orphan Grace takes care of her older but mentally unfit sister Lily, and after enduring many harsh and painful experiences, the two become the victims of a fraud perpetrated by the wealthy owners of several funeral businesses